Informação e segurança pública: a construção do conhecimento social em um ambiente comunitário - Marco Antonio de Azevedo (2006)
This researchs objective was to describe the processes of construction of social knowledge that take place in the communitys environments that aim to promote public safety. It was considered that the military policies are in crisis (of knowledge) facing the escalation of criminality and that the adoption of a community model of police action, more compatiblewith the values of a democratic society, is a viable alternative. The new model presupposes the redefinition of the polices roles and demands the construction of new knowledge, oriented to preventive strategies, intense exchange of information with the community and the development of public safety indexes using technologies of information systems. The informational phenomena was discussed as a social construction, showing that is the individual information user, limited by the political-historical-cultural context, who selects the meanings, builds knowledge and generates new information. Starting from an exploratory study, it was defined as the focus of the investigation would be the informational practices that take place in a Consep (Community Counsels of Public Safety) in Belo Horizonte, community organization that is important for the establishment of community policing. To analyze these questions, the theoreticalmethodological notion of third knowledge, and the construct of anthropology of information, that allows for the study of the information in movement, were used as areference. The field work was guided by the hermeneutic-dialectic method, as described by Minayo (2002); by an ethnographic attitude, as necessary to elaborate a thick description, as described by Geertz (1978) and by the theory of the social camp developed by Bourdieu(1991, 2002). The results evidenced that there are different manners to experience and conceive violence, and that the information, as a way to communicate the experience, is the object of symbolic disputes within the Consep studied. The informational poles go on conflict anddifficulties to share information take place, characterizing what is called an informational emptiness.